SOYBEAN SEEDS PERFORMANCE COATED WITH HIDROPHYL POLYMERS (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The use of biodegradable and biocompatible polymers in seeds coated has become important due to their desirable and renewable biological properties. The present study aimed to evaluate the effect of biopolymers on the imbibition and physiological attributes of soybean seeds, NK 7059 RR cultivar. The seeds were coated with cassava starch, sodium alginate and polyvinyl alcohol biopolymers at four different concentrations 0, 2, 4 and 6%. The imbibition was evaluated at three hour intervals for 24 hours, totaling eight evaluations. For physiological quality the seeds were submitted to the tests of first germination count, germination, germination speed index, accelerated aging, greenhouse emergence, emergence speed index and electrical conductivity. The polymers used in the present study increase the percentage of seed soaking, especially sodium alginate at a concentration of 4%. Sodium alginate coating affects the physiological quality of seeds. In general, the higher the polymer concentration, the greater the negative interference on seed physiological performance.